William Congreve : the critical heritage - Lindsay, Alexander, 1952-; Erskine-Hill, Howard (Critical heritage series., 1989)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling student and researcher to read the material themselves.